2015
DOI: 10.1007/s12199-015-0444-8
|View full text |Cite
|
Sign up to set email alerts
|

Sexual orientation and smoking history: results from a community-based sample of youth in Shanghai, China

Abstract: Objective Cigarette smoking has been found to be more prevalent among adults and youths with a minority sexual orientation (lesbian, gay, bisexual, LGB) than among the general population, while less is known about smoking among LGB youth in low-and middle-income countries. The goal of the study was to examine cigarette smoking in relation to sexual orientation in a community-based sample of youth in Shanghai, China. Methods A multi-center cross-sectional survey of 17,016 youth aged 15-24 years was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Although few Chinese studies have explicitly examined the mechanism between minority stress and cigarette use [13,14,54], qualitative research has suggested that Chinese sexual minority men may use substances to relieve the stress of hostile social stigma, as well as familial and cultural pressures [55]. Therefore, it is important to empirically examine speci c pathways through which minority stressors might in uence cigarette use among Chinese sexual minorities, particularly gay and bisexual men.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although few Chinese studies have explicitly examined the mechanism between minority stress and cigarette use [13,14,54], qualitative research has suggested that Chinese sexual minority men may use substances to relieve the stress of hostile social stigma, as well as familial and cultural pressures [55]. Therefore, it is important to empirically examine speci c pathways through which minority stressors might in uence cigarette use among Chinese sexual minorities, particularly gay and bisexual men.…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to the growing body of literature examining the heterogeneity of sexual minority stressors and subsequent psychological and health behavior risks across sexual minority subgroups in North America, very little is known about this topic in China. One 2015 paper by Lian et al in China studied smoking among sexual minority youth and actually found the reverse pattern, that male bisexual and heterosexual youth shared similar smoking patterns while gay youth reported higher smoking rates compared to heterosexual counterparts [13]. Lian and colleagues believed that bisexual youth in China might be less involved with…”
Section: Introductionmentioning
confidence: 99%
“…Other research by Sweet and Welles (2012) indicates that bisexual men may experience signi cantly more adverse childhood experiences compared to gay men [58]. However, in China, a 2015 study has documented the reverse pattern, that male bisexual and heterosexual youth shared similar smoking patterns while gay youth reported higher smoking rates compared to heterosexual counterparts [13].…”
mentioning
confidence: 97%
“…In Eastern Asian countries like China, the Minority Stress Theory has been almost exclusively applied to predicting physiological outcomes [50][51][52][53]. Although few Chinese studies have explicitly examined the mechanism between minority stress and cigarette use [13,14,54], qualitative research has suggested that Chinese sexual minority men may use substances to relieve the stress of hostile social stigma, as well as familial and cultural pressures [55].…”
mentioning
confidence: 99%
“…In Eastern Asian countries like China, the Minority Stress Theory has been almost exclusively applied to predicting physiological outcomes [50][51][52][53]. Although few Chinese studies have explicitly examined the mechanism between minority stress and cigarette use [13,14,54], qualitative research has suggested that Chinese sexual minority men may use substances to relieve the stress of hostile social stigma, as well as familial and cultural pressures [55]. Therefore, it is important to empirically examine speci c pathways through which minority stressors might in uence cigarette use among Chinese sexual minorities, particularly gay and bisexual men.…”
mentioning
confidence: 99%